The effect of fiscal and monetary policies interaction on stock market performance: Evidence from Nigeria - Adedoyin Isola Lawal; Russell Olukayode Somoye; Abiola Babajide; Tony Ikechukwu Nwanji (Future Business Journal, 2018)
This study examines the impact of the interactions between fiscal and monetary policies on stock market behaviour (ASI) and the impact of the volatility of these interactions on the Nigerian stock market. The study analysed monthly data using the ARDL and EGARCH models. The results show the interaction between monetary and fiscal policies influence on stock market returns in Nigeria. The ARDL results show evidence of long run relationship between ASI and Monetary-fiscal policies. The results from the volatility estimates show that the ASI volatility is largely sensitive to volatility in the interactions between the two policy instruments. The results suggest calibrating both the monetary and fiscal policies in a single model when formulating stock market policy as their interaction exerts significantly on stock market behaviour, thus both policies should be considered in tandem.
Keywords: E52; E63; 650; ARDL; EGARCH; Fiscal-monetary policy; Nigeria; Stock market